Dimuridkan oleh Algoritma, Digembalakan oleh Media Sosial: (Sebuah Refleksi Kritis Peran Pendidikan Agama Kristen Dalam Keluarga) - Legi, Hendrik; Giban, Yoel; Kainara, Semi (STT INDONESIA MANADO, 2025)
Abstract: The rapid development of digital technology has brought significant changes in the lifestyle of Christian families, especially in the process of child discipleship. Social media algorithms now play a dominant role in shaping children's behaviors, thoughts, and moral values, replacing the traditional role of the family as the center of faith education. This situation raises important questions. What is the role of Christian Religious Education (PAK) in the family in facing the challenges of algorithms and the dominance of social media in the process of forming children's faith? This research aims to critically reflect on the role of PAK in the Christian family in the context of an increasingly complex digital age. The research method used is a reflective qualitative approach with literature study and content analysis. The study found that many Christian families tend to let algorithms be the primary